RE-EPITELISASI LUKA SOKET PASCA PENCABUTAN GIGI SETELAH PEMBERIAN GEL GETAH PISANG RAJA (Musa sapientum L) Kajian histologis pada marmut (Cavia cobaya) - Juwita Raditya Ningsih; Tetiana Haniastuti; Juni Handajani (Muhammadiyah University Press, 2019)
ABSTRACTGingival epithelium has an important role in the protection of the gingival tissue from mechanical, physical, and chemical trauma also microbial invasion. Re-epithelialization is an important phase of post extraction socket healing. Previous study showed that banana (Musa sapientum L) latex containing tanin, saponin, flavanoid, vitamin C, and minerals i.e: kalium, magnesium, calcium induced re-epithelialization in skin wounds. The objective of the present research was to study the effectivity of banana latex gel in the re-epithelialization of post extraction socket in guinea pigs (Cavia cobaya).Fifty four guinea pigs were divided into 3 groups, there were negative control group, positive control group and banana latex gel group. Each group consisted of 18 guinea pigs. Mandibular left central incisive were extracted and CMC-Na 1% (negative control), iod-glycerin (positive control) and banana latex gel were applied into the wound socket. Guinea pigs were then sacrified at 1,3,5,7,14,24 day post extraction and processed for histological examination. The specimens were stained with hematoxilin eosin. Epithelial thickness was measured with optilab (µm). The result of Anova showed significant differences in epithelial thickness among groups (p0,05). Least Significant of Difference test showed significant differences (p0,05) at 3,5,7,14,24 day post extraction between banana latex gel group compared to negative control group and also at 7 and 24 day post extraction between banana latex gel group compared to positive control group. In conclusion, banana latex gel may induce re-epithelialization of post extraction socket. The effect of banana latex gel is similar to iod-glycerin.Key words: re-epithelialization, banana latex gel, tooth socket